BENTUK PENYAJIAN TARI PEGAWAI DALAM PESTA PERKAWINAN DI KAMPUNG HULU PASA MALINTANG NAGARI INDERAPURA TENGAH KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN - Maysa Anggelia Putri; Susmiarti (Universitas Negeri Padang, 2026)
This study aims to describe and reveal the presentation form of the Employee Dance in wedding celebrations in Kampung Hulu Pasa Malintang, Nagari Inderapura Tengah, Pancung Soal District, South Coastal Regency. This type of research is qualitative with a descriptive method. The research instrument is the researcher themselves, assisted by writing tools and a camera. Data were collected through literature studies, observation, interviews and documentation. The steps in analysing the data are collecting data, reducing data, presenting data, and drawing conclusions. The research results show that the form of presentation of the Employee Dance in wedding celebrations in Kampung Hulu Pasa Malintang includes various interconnected elements that form a cohesive and meaningful performance, including movements, floor design, music design, dancers, costumes, props and the performance venue. The movements of the Employee Dance consist of Long Step movements, right side movements, left side movements, and Ninjau movements. The floor pattern of the Employee Dance is merely a development of a straight line. The accompanying music of the Employee Dance consists of musical beats and chants. The musical instrument used is the rebana. The Employee Dance is performed by seven male dancers who are either adults or middle-aged. The dancers wear batik clothes freely without specific patterns or colour requirements, while their lower attire consists of neatly wrapped sarongs in place of trousers. The property used in the Employee Dance is a long cloth. The Employee Dance is performed inside the house where the traditional wedding ceremony takes place, specifically in front of the bride and groom standing on a prayer mat.